2014
DOI: 10.1002/oby.20816
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypertriglyceridemia: A link between maternal overweight-obesity and macrosomia in gestational diabetes

Abstract: Objective: Infants born from overweight and obese mothers with glucose-controlled gestational diabetes (GDM) tend to be large-for-gestational age (LGA). It is hypothesized that this is due to an excessive rise in maternal triglyceride levels. Methods: Two-hundred and seventy nine singleton GDM pregnancies were divided into three groups according to prepregnancy BMI: normal weight (BMI 5 20-24.9; n 5 128), overweight (BMI 5 25-29.9; n 5 105), and obese (BMI 30; n 5 46). Individual z-scores (ZS) of maternal trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
5
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 22 publications
4
46
5
5
Order By: Relevance
“…Furthermore, we note the possibility that pathogenic effects in pregnant women with an abnormally high TCh concentration may result from an increased synthesis of other compounds that are capable of crossing the placental barrier. Other research groups reported a positive correlation between the maternal triglyceride concentration and the weight or fat mass of the newborn in pregnancies with gestational diabetes mellitus [9,41,42] or with overweight and obese mothers with gestational diabetes mellitus [43]. Our results show no correlation between the maternal triglyceride concentration, as well as for any of the lipoproteins analyzed in this study, and the newborn weight from normal pregnancies (i.e., without diagnosis of gestational diabetes mellitus or obesity).…”
Section: Discussioncontrasting
confidence: 70%
“…Furthermore, we note the possibility that pathogenic effects in pregnant women with an abnormally high TCh concentration may result from an increased synthesis of other compounds that are capable of crossing the placental barrier. Other research groups reported a positive correlation between the maternal triglyceride concentration and the weight or fat mass of the newborn in pregnancies with gestational diabetes mellitus [9,41,42] or with overweight and obese mothers with gestational diabetes mellitus [43]. Our results show no correlation between the maternal triglyceride concentration, as well as for any of the lipoproteins analyzed in this study, and the newborn weight from normal pregnancies (i.e., without diagnosis of gestational diabetes mellitus or obesity).…”
Section: Discussioncontrasting
confidence: 70%
“…Because SM is the principal tissue for both insulin-mediated glucose disposal 17 and fatty acid oxidation 18 and an essential element of energy metabolism, 80 the progressive reductions in maternal PA and PAEE over the past century would result in progressive decrements in metabolic, 17,29,31,8183 glycemic, 8385 and lipidemic control. 8688 This loss of metabolic control led to both transient hyperglycemia (i.e., glycemic excursions) and hyperlipidemia, 8991 the former driven by reductions in insulin signaling resulting from replete myocyte glycogen stores, 92,93 and the latter from reduced SM energy demands and consequent decrements in total fatty acid oxidation, 8688,94 increments in hepatic and adipocyte de novo lipogenesis, 9597 and lipid accumulation in adipose tissue. 98,99 …”
Section: The Maternal Resources Hypothesis (Mrh)mentioning
confidence: 99%
“…103 I posit that the progressive reductions in maternal PA and PAEE and consequent reductions in SM activation over the past half century act synergistically with the naturally occurring metabolic sequelae of pregnancy (i.e., hormone-induced insulin resistance, increased adiposity) to exacerbate the negative metabolic consequences of inactivity 29,30,100,101 and drive fetal pathologies. The reductions in insulin sensitivity and increments in transient hyperglycemia and hyperlipidemia 91 substantially increase the availability of energy substrates to the intrauterine environment. Because the human placenta evolved in a context of intense competition between maternal resources and fetal demands (i.e., low to moderate maternal body mass and adiposity in concert with moderate to high levels of maternal EE, PA, and PAEE 104–106 ), the current context of high maternal resources in combination with low PA represents an evolutionary mismatch.…”
Section: The Maternal Resources Hypothesis (Mrh)mentioning
confidence: 99%
“…17, 43 Such associations have also been observed in patients with gestational diabetes. 44,45 However, data on triglyceride levels during pregnancy in women with type 1 diabetes are limited. 13 There is a paucity of data from human trials exploring the role of CSII on the lipid profile in patients with type 1 diabetes.…”
Section: Resultsmentioning
confidence: 99%